Special or Hybrid Courts and Residual Mechanisms in the International Criminal Justice System - Loayza Tamayo, Carolina (2020)
The fight against impunity for serious human rights violations and the establishment of a permanent international criminal court have been a constant since the Second World War. At the end of the 20th century and the beginning of the 21st century, new international criminal jurisdictions were established in addition to a permanent international criminal court, the Special Tribunals to avoid leaving unpunished serious human rights violations of international law, that occurred during the cold war and the Residual Mechanisms as a part of strategy to end all temporary international criminal jurisdiction activity established post Cold War. Both urisdictions, although temporary, recognize the importance of national justice and aim to strengthen the international criminal justice system.